Correlation and Path Coefficient Studies for Plant Characters in Aqua Aroids, Colocasia esculenta (L.) Schott - Paul, K. K.; Bari, M. A.; Debnath, S. C. (Journal of Scientific Research, 2010)
The nature and extent of correlation and path coefficients of aqua edible aroid taro (Colocasia esculenta L., Panikachu) accessions were studied for plant height, petiole length, petiole breadth, leaf number, leaf length, leaf breadth, leaf area index, inflorescence length, peduncle length, spath length, spath breadth and yield per plant. The yield per plant showed significant and positive phenotypic correlation with petiole length (0.481), leaf length (0.576), leaf breadth (0.918), leaf number (0.620), inflorescence length (0.662), spath length (0.890) and spath breadth (0.992). The residual effect was 0.2205 which indicated that characters studied contributed 78% of yield per plant. At genotypic level, yield per plant expressed positive and significant correlation with plant height (0.560) and leaf number (0.600). The residual effect (0.424) indicated that about 58% yield was contributed by these characters. Keywords: Genotypic correlation; Phenotypic correlation; Path coefficient; Aqua aroid; Panikachu (Colocasia esculenta L Schott.stoloniferous). © 2011 JSR Publications. ISSN: 2070-0237 (Print); 2070-0245 (Online). All rights reserved. doi:10.3329/jsr.v3i1.6078 J. Sci. Res. 3 (1), 169-176 (2011)